Controversies in Parenteral Protein Intake in Preterm Infants - Ira Holla; Pradeep Alur (Children, 2025)
As the limit of viability is extended to lower gestational ages, neonatologists caring for preterm infants must discover the optimal nutritional combination to support postnatal growth. It has been well established that introducing protein soon after birth is associated with improved short-term growth at 36 weeks postmenstrual age and neurodevelopment. However, it remains unclear what the optimal level of protein is for parenteral nutrition at various gestational ages. Several studies have shown possible adverse effects of high-protein delivery in very low birth weight infants. Inborn errors in amino acid metabolism also caution us that higher levels of specific amino acids can harm the growing brain.